Pemanfaatan Limbah Minyak Goreng sebagai Upaya Pemberdayaan Ekonomi Masyarakat Sedati Sidoarjo - Saleh, M.; Pramudya, Sendi (Bisma : Bimbingan Swadaya Masyarakat, 2023)
The purpose of this community service is to reduce the generation of fried waste in Sedati Sidoarjo. Through a community development approach, the results of this service have succeeded in making the Used Cooking Oil Saving Movement. The door to door approach is carried out as part of the service and convenience for residents to participate in the used cooking saving movement in Sedati Sidoarjo